Expression of nuclear factor, erythroid 2-like 2-mediated genes differentiates tuberculosis. (July 2016) - Qian, Zhongqing; Lv, Jingzhu; Kelly, Gabriel T.; Wang, Hongtao; Zhang, Xiaojie; Gu, Wanjun; Yin, Xiaofeng; Wang, Ting; Zhou, Tong
Summary: During infection and host defense, nuclear factor, erythroid 2-like 2 (Nrf2) dependent signaling is an efficient antioxidant defensive mechanism used by host cells to control the destructive effects of reactive oxygen species. This allows for effective defense responses against microbes while minimizing oxidative injury to the host cell itself. As a central regulator of antioxidant genes, Nrf2 has gained great attention in its pivotal role in infection, especially in tuberculosis (TB), the top infectious disease killer worldwide. To elucidate the genes potentially regulated by Nrf2 in TB, we conducted a meta-analysis on published gene expression datasets. Firstly, we compared the global gene expression profiles between control and Nrf2-deficient human cells. The differentially expressed genes were deemed as "Nrf2-mediated genes". Next, the whole blood gene expression pattern of TB patients was compared with that of healthy controls, pneumonia patients, and lung cancer patients. We found that the genes deregulated in TB significantly overlap with the Nrf2-mediated genes. Based on the intersection of Nrf2-mediated and TB-regulated genes, we identified an Nrf2-mediated 17-gene signature, which reflects a cluster of gene ontology terms highly related to TB physiology. We demonstrated that the 17-gene signature can be used to distinguish TB patients from healthy controls and patients with latent TB infection, pneumonia, or lung cancer. Also, the Nrf2-mediated gene signature can be used as an indicator of the anti-TB therapeutic response. More importantly, we confirmed that the predictive power of the Nrf2-mediated 17-gene signature is significantly better than the random gene sets selected from the human transcriptome. Also, the 17-gene signature performs even better than the random gene signatures selected from TB-associated genes. Our study confirms the central role of Nrf2 in TB pathogenesis and provides a novel and useful diagnostic method to differentiate TB patients from other human subjects.